Konstruksi keluarga sakinah dalam al-quran qs.ar-rum 21 - Ramadhani, Dina (Maliki Interdisciplinary Journal, 2026)
This study looks at the idea of a sakinah family as mentioned in QS. Ar-Rūm [30]:21. It focuses on three main parts: the spiritual, psychological, and social sides of family life. The research uses a qualitative approach, mainly based on studying existing literature. The main sources of information come from the Qur'an and related tafsir books. Additional information is taken from scientific articles, theses, and research found in the UIN Maulana Malik Ibrahim Malang Repository. The study found that sakinah in this verse isn't just about being calm or happy, but it also refers to an inner peace that comes from practicing tawhid, viewing marriage as a form of worship, and having social interactions based on love and kindness. The vertical part, which is the relationship with God, is the main cause of inner peace. The horizontal part is seen in the good relationship between a husband and wife through talking, understanding, and showing love. The study concludes that a sakinah family is formed when there is spiritual obedience, emotional growth, and the use of Qur'anic values in everyday life. Therefore, QS. Ar-Rūm [30]:21 can guide people in creating a strong, peaceful, and lasting family.